PENGARUH BRAND AWARENESS DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK BRAND FASHION LOKAL SLASHROCK GEAR DI KOTA DENPASAR - I Made Surya Prayoga; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2024)
Purchase decision is the thought process that leads a consumer from identifying a need, generating options, and choosing a specific product and brand. This study aims to analyse the effect of brand awareness and perceived quality on purchase decision of local fashion brand Slashrock Gear in Denpasar. This research was conducted on all consumers of Slashrock Gear in Denpasar. The sampling method used a purposive sampling, with a sample size of 75 consumers. Data analysis used is multiple linear regression analysis. The results showed that brand awareness and perceived quality has a positive and significant impact on purchase decision of local fashion brand Slashrock Gear in Denpasar. The upcoming study can utilize another independent variables, such a promotion, price, or other variables which has impact on purchase decision theoretically